Effects of Lactobacillus Reuteri Lozenges (Prodentis) as Adjunctive Therapeutic Agent in Non-Surgical Therapy of Periodontitis - Hadžić Zerina; Pašić Enes; Vukelić Mirjana Gojkov; Hadžić Sanja (Balkan Journal of Dental Medicine, 2021)
Background/Aim: This study aimed to evaluate the effects of Lactobacillus reuteri lozenges as an adjunctive therapeutic agent in combination with scaling and root planing in a randomized, clinical trial of volunteers with periodontitis stage IV.